2022
DOI: 10.1080/10717544.2022.2120566
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody as a targeting mediator for nanoparticle targeted delivery system for lung cancer

Abstract: Lung cancer is the second most common type of cancer after breast cancer. It ranks first in terms of mortality rate among all types of cancer. Lung cancer therapies are still being developed, one of which makes use of nanoparticle technology. However, conjugation with specific ligands capable of delivering drugs more precisely to cancer sites is still required to enhance nanoparticle targeting performance. Monoclonal antibodies are one type of mediator that can actively target nanoparticles. Due to the large n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…A number of studies have been conducted on nanoparticles as passive delivery routes for cancer therapy, particularly for lung cancer. Cancer cells can be precisely identified using this targeting mechanism by interacting with specific ligands and receptors expressed abundantly in cancer cells (Wathoni et al, 2022). Ongoing and completed clinical trials have already reported positive results using nano-immunotherapy, and preclinical studies have also demonstrated significant improvements in therapeutic efficacy (Sun et al, 2020).…”
Section: Nanoparticles In Lung Cancer Immunotherapymentioning
confidence: 99%
“…A number of studies have been conducted on nanoparticles as passive delivery routes for cancer therapy, particularly for lung cancer. Cancer cells can be precisely identified using this targeting mechanism by interacting with specific ligands and receptors expressed abundantly in cancer cells (Wathoni et al, 2022). Ongoing and completed clinical trials have already reported positive results using nano-immunotherapy, and preclinical studies have also demonstrated significant improvements in therapeutic efficacy (Sun et al, 2020).…”
Section: Nanoparticles In Lung Cancer Immunotherapymentioning
confidence: 99%
“…1 In addition to targeted peptides, monoclonal antibodies can also be used to deliver nanoparticles to the lung and bind to the corresponding overexpressed receptors, such as epidermal growth factor receptor (EGFR), epithelial cell adhesion molecule receptor, etc. 144 Some monoclonal antibodies against lung cancer have been reviewed for selectively targeting the lung cancer after decorating on nanoparticles. 144 In addition to active targeting, endogenous targeting also strongly influences the accumulation of nanoparticles in the lung, where the composition and structure of nanoparticles significantly affect their endogenous targeting.…”
Section: Lungmentioning
confidence: 99%
“…144 Some monoclonal antibodies against lung cancer have been reviewed for selectively targeting the lung cancer after decorating on nanoparticles. 144 In addition to active targeting, endogenous targeting also strongly influences the accumulation of nanoparticles in the lung, where the composition and structure of nanoparticles significantly affect their endogenous targeting. 9 Siegwart et al found that the addition of 50% permanent cationic lipids to LNPs greatly increased the amount of LNPs in the lungs.…”
Section: Lungmentioning
confidence: 99%
See 2 more Smart Citations